NARRATIVE STRATEGIES AGAINST UNITY & CONTINUITY: THE CASE OF FOCALISATION IN VEDIC & MODERN DAY DHRUPAD VOCAL MUSIC STORIES - Subroto Mihirchandra Roy (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
Narratives that we hear, connect dots to complete a civilisational story. Narrative strategies on Indian heritage of about 1000 years need to be revisited as newer counter narratives need to be factored in. If we examine our case of Sa?m Veda (ancient Veda singing date not known) and Dhrupad (probably from around 300 BC and still extant) through a natively ordered narrative framework. However, newer globalised narratives are ordered in such a manner that the story sounds strange to natives. The paper points out that this might often not be a clash of historical method and tradition, but focalisation or mere agenda. Also we often see narrators may not represent knowledge, being mistaken for the source of knowledge. For instance, a person trained in the Khaya?l singing tradition telling the story of Dhrupad or even Sa?ma Ga?na. This may involve focalisation.